The Effectiveness of 4% Niacinamide in A Case of Cutaneous Lupus - Anggun Putri Yuniaswan; Belladikna Brillianty Sugiatno (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: Niacinamide, also called nicotinamide, is the active form of niacin (nicotinic acid, vitamin B3). Niacinamide’s role in medicine continues to be studied due to its extensive effects and low toxicity. Various studies also suggest that niacinamide offers anti-inflammatory effects, improves the skin barrier, and acts as an anti-aging, brightening, and anticancer agent. Cutaneous lupus (CL) is a general term for a group of autoimmune connective tissue disorders affecting the skin that may be associated with systemic lupus erythematosus (SLE). There are plenty of treatment modalities for patients with CL, each with varying efficacy. Therapeutic options for CL can range from topical agents, including corticosteroids and calcineurin inhibitors, to systemic therapy, such as antimalarials, immunosuppressants, retinoids, thalidomide, and biological agents. Niacinamide is a topical agent widely used in various cases, one of which is CL. Objective: This case report aims to discuss the effectiveness of niacinamide as an adjuvant therapy in CL. Case Presentation: A 48-year-old woman with SLE and CL received systemic therapy consisting of methylprednisolone, hydroxychloroquine, and 4% niacinamide gel for 8 weeks. Results: Observations showed clinical improvement in CL lesions without any significant side effects. Conclusion: Therefore, 4% niacinamide gel therapy can be used as an adjuvant therapy.